RESEÑA de : Martínez Torres, José Antonio. Esclavos, Imperios, Globalización (1555-1778). Madrid : Consejo Superior de Investigaciones Científicas, 2010 - Gómez Vozmediano, Miguel Fernando (Espacio Tiempo y Forma. Serie IV, Historia Moderna, 2010)
-